Facial vertical changes among patients treated by Edgewise orthodontic technique along with tooth extraction - Heravi F.; Sahafian Sh (Tehran University of Medical Sciences, 2004)
Statement of Problem: Tooth extraction is a common technique in orthodontics and most of the specialists believe that this technique is able to change the facial appearance. Purpose: The aim of this study was to investigate facial vertical changes in orthodontic patients following tooth extraction. Materials and Methods: Thirty patients, after their growth spurt, with CLI malocclusion all treated by a specific orthodontist through Edgewise technique along with the extraction of four first premolars were chosen. Lateral cephalograms of patients, before and after treatment were compared and facial vertical changes and teeth were studied. Results: Anterior and posterior facial heights were increased during treatment. Despite the limited use of intermaxillary elastics, teeth were extruded. The most increase in facial heights was observed in the lower third of face. Patients with longer faces before treatment showed more extrusion of mandibular molars as well as more increase of mandibular slope. Conclusion: Tooth extraction in orthodontic treatments can not guarantee the decrease or even non-increase of facial height. Among patients with long faces, it is particularly suggested to refrain from the application of extrusive orthodontic forces.